2017
DOI: 10.1192/bjpo.bp.117.005322
|View full text |Cite
|
Sign up to set email alerts
|

Mental health difficulties and suicidal behaviours among young migrants: multicentre study of European adolescents

Abstract: BackgroundMigration has been reported to be associated with higher prevalence of mental disorders and suicidal behaviour.AimsTo examine the prevalence of emotional and behavioural difficulties, suicidal ideation and suicide attempts among migrant adolescents and their non-migrant peers.MethodA school-based survey was completed by 11 057 European adolescents as part of the Saving and Empowering Young Lives in Europe (SEYLE) study.ResultsA previous suicide attempt was reported by 386 (3.6%) adolescents. Compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 29 publications
(39 reference statements)
1
33
0
Order By: Relevance
“…These indeed are relevant to the current study as most immigrants in Sweden consist of refugees, asylum seekers, and/or unskilled labor workers [5]. We suggest that other European studies indicating poorer mental health among immigrant adolescents compared to native peers e.g., [4,[6][7][8] may share this underlying reason to some degree.…”
Section: Mental Health Among Immigrant and Native Adolescentsmentioning
confidence: 66%
See 1 more Smart Citation
“…These indeed are relevant to the current study as most immigrants in Sweden consist of refugees, asylum seekers, and/or unskilled labor workers [5]. We suggest that other European studies indicating poorer mental health among immigrant adolescents compared to native peers e.g., [4,[6][7][8] may share this underlying reason to some degree.…”
Section: Mental Health Among Immigrant and Native Adolescentsmentioning
confidence: 66%
“…Indeed, this was the case in, for example, Norway, Spain and Italy [4,6,7]. A recent study conducted in ten European countries also reported more mental health problems among immigrant adolescents than their native peers [8].…”
Section: Mental Health Of Immigrant Adolescentsmentioning
confidence: 95%
“…The large and growing burden of mental health and substance use disorders among older children and adolescents also is an emerging threat to the thrive component of the SDG survive and thrive agenda. While the psychological needs of children and adolescents show similarities across geographical settings, 24 , 25 , 26 , 27 comparatively little is understood about modifiable risk factors or effective prevention programs for childhood mental illness, outside of ensuring that caregivers are attuned to the link between mental health disorders and self-harm. 28 , 29 Injuries in general continue to be a major cause of early mortality and long-term disability among older children and adolescents in all countries.…”
Section: Discussionmentioning
confidence: 99%
“…These include patient-related risk factors, such as social, economic and cultural factors, male gender, alcohol intoxication, substance abuse, mental disorder, and language barrier that leads to frustration [ 20 , 22 , 23 , 24 ]. These factors are often found in migrants, especially those who originate from low- and middle-income countries [ 25 ]. With these reasons and the recent increase of patients with migratory backgrounds seeking ED assistance, as well as previous reports indicating that migrants are prone to be at higher risk for aggressive behavior [ 26 ], the aim of this study was to define the incidence of and characterize cases of WPV that were reported at the ED of a Swiss university hospital.…”
Section: Introductionmentioning
confidence: 99%